Food environment in and around schools and colleges of Delhi and National Capital Region (NCR) in India - Shalini Bassi; Deepika Bahl; Monika Arora; Fikru Tesfaye Tullu; Sakshi Dudeja; Rachita Gupta (BMC, 2021)
Abstract Background Food policies and environment (availability, accessibility, affordability, marketing) in and around educational institutes can influence food choices and behaviours of children and adolescents. Methods Cross-sectional, mixed-methods study was implemented in schools (n = 9; Private = 6, Public = 3) and colleges (n = 4) from Delhi and National Capital Region (India). The data was collected from students of schools (n = 253) and colleges (n = 57), parents of school students (n = 190), teachers (n = 12, schools = 9, colleges = 3) and canteen operators of Private schools and colleges (n = 10; schools = 6, and colleges = 4). The primary and secondary data was collected to: 1) identify the strengths and weaknesses of the existing guidelines and directives (desk review); 2) examine food environment, existing policies and its implementation (structured observations, in-depth interviews, surveys, focus group discussions), and; 3) assess food choices, behaviours of students (focus group discussions). The thematic analysis was used for qualitative data and descriptive analysis for quantitative data. Results The available food and beverage options, in and around the participating educational institutes were either high in fat, salt and sugar (HFSS), despite government and educational institute guidelines on restricting the availability and accessibility of HFSS foods. The healthy food and beverage options were expensive compared to HFSS foods both inside and outside educational institutes. In total, 37 vendors (Private = 27; Public:10) were observed outside schools at dispersal and twelve at lunchtime. Around colleges, vendors (n = 14) were seen throughout the day. Students from all Private schools (n = 6) and colleges (n = 2) were exposed to food and beverage advertisements either HFSS (Private schools = 1-3 and colleges = 0-2 advertisements), whereas no advertisements were observed around Public schools. Conclusion It is imperative to implement food policies to improve the food environment in and around educational institutes to ensure the availability of healthy foods to establish and sustain healthy eating behaviours among students. Thus, the study findings emphasise stringent implementation, regular monitoring and surveillance of recently introduced Food Safety and Standards (Safe food and balanced diets for children in school) Regulation 2020, ensuring its compliance through effective enforcement strategies.